Closed nuclear fuel cycle strategy for NuScale-like reactor: safety parameters evaluation - Keferson Almeida; Graiciany de Paula Barros; Matheus Henrique dos Santos Araújo; Rebeca Cabral Gonçalves; Tiago Augusto Santiago Vieira; Vitor Silva; Andre Augusto Campagnole dos Santos (Brazilian Journal of Radiation Sciences)
The present study evaluates the potential implementation of two different closed fuel cycle strategies for a NuScale-like reactor core. After undergoing three burnup cycles of approximately 12 MWd/kgU in the NuScale-like initial core and five years of cooling in a spent fuel pool, the spent fuel was theoretically reprocessed using GANEX or UREX+ methods. These reprocessed fuel compositions were then mixed with thorium (Th) and inserted into specific batch positions of the core. As a result, the proposed NuScale-like core configurations contain fuel assemblies loaded with both conventional uranium-based fuel and reprocessed fuel, resulting in the following combinations: UO2 and GANEX spiked with Th, and UO2 and UREX+ spiked with Th. The primary goal is to assess the safety margins of the proposed cores and compare them with the reference case. The results indicate that all scenarios with reprocessed fuel improved the fuel temperature reactivity coefficient and maximum initial excess of reactivity, while varying the boron concentration in the coolant. Additionally, it was found that both proposed cores met the power peak factor (PPF) design requirements, despite the high PPF value observed at the C03 central position. The simulations were performed using the Serpent code version 2.1.32, developed by VTT.